*

*

See that if $$e^x=y\ implies e^-x = frac1y\ indicates -x = lnleft(frac1y ight) \ implies x = -lnleft(frac1y ight)$$


*

*

Tright here are several means to display this.$$ ln frac12 = ln 2^-1 = -1 cdot ln 2 = - ln 2 ext. $$

$$ ln frac12 = ln 1 - ln 2 = 0 - ln 2 = - ln 2 ext. $$

Using your reality, expect $ln frac12 = x$, then $frac12 = occupychristmas.orgrme^x$, so $2 = frac1occupychristmas.orgrme^x = occupychristmas.orgrme^-x$. But this claims, utilizing your fact aobtain, $ln 2 = -x$, so $x = - ln 2$.

You are watching: Ln(-1/2)


*

Suppose $$x=lnleft(frac 1 2 ight)$$then $$e^x=frac 1 2 = 2^-1$$So$$e^-x=2$$Hence, $$-x=ln2$$providing $$x=-ln2$$

In basic, let $z=lnleft(y^n ight)$.We have$$ e^z=y^n$$So$$ e^z/n=y$$giving$$frac z n=ln y$$Hence,$$lnleft(y^n ight)=z=nln y$$


Thanks for contributing an answer to occupychristmas.orgematics Stack Exchange!

Please be sure to answer the question. Provide details and share your research!

But avoid

Asking for help, clarification, or responding to various other answers.Making statements based upon opinion; ago them up through references or personal experience.

Use occupychristmas.orgJax to format equations. occupychristmas.orgJax referral.

See more: Which Is The Superior Observational Study? Why? Choose The Correct Answer Below.

To learn even more, check out our tips on creating good answers.


Article Your Answer Discard

By clicking “Blog post Your Answer”, you agree to our terms of business, privacy policy and also cookie plan


Not the answer you're looking for? Browse other questions tagged logarithms or ask your very own question.


website design / logo © 2021 Stack Exadjust Inc; user contributions licensed under cc by-sa. rev2021.9.14.40215


Your privacy

By clicking “Accept all cookies”, you agree Stack Exreadjust have the right to keep cookies on your tool and also disclose information in accordance through our Cookie Policy.